Determinants of Motivating Muslims to Become Entrepreneurs in Malaysia - Rosnia Masruki; Nurazalia Zakaria; Nuradli Ridzwan Shah Mohd Dali; Siti Nurulhuda Nordin; Norasikin Salikin (Universiti Sains Islam Malaysia, 2024)
This paper discusses the factors that motivate Muslims to become entrepreneurs in various states throughout Malaysia. In 2009, a semi-structured interview of 150 Muslim entrepreneurs who are involved in a wide range of business activities was done throughout the various states in Malaysia. Grounded theory methodology was applied to identified the possible reasons behind their decision to become an entrepreneur. The findings suggested that passion and interest in managing own business greatly explain the motivation for people to be involved in entrepreneurship. The passion guided them to overcome obstacles and challenges arising from competitions and ensuring sustainability of the business. The second reason wasJinancia1 consideration or income generation from the business as this will be eventually used to support their families and improve their condition of life. The third reason was the independence and freedom that self-employment provides as compared to being employed in the private or public sector. Other notable reason was their family background since many of the entrepreneurs came from families that own businesses. The results of this study calls for the academia to develop teaching methods and conduct students ' activities that helps to fosters students' interest and passion in the field of entrepreneurship. Future research in this area might be an exploration on the differing attributes such work ethics, work culture, decision making behaviour of Muslim and non-Muslim entrepreneurs.